Validitas e-module Berbasis Inkuiri Terbimbing Terintegrasi Al-Qur’an pada Materi Laju Reaksi Kelas XI Madrasah Aliyah - Hendriko, Hendriko; Iryani, Iryani (Edukimia, 2022)
In this study, the validity of the e-module based on the integrated guided inquiry of the Quran was tested on the material for the reaction rate of class XI Madrasah Aliyah. This is an Educational Design Research with a few stages, which is preliminary research, prototyping, and assessment included in the Plomp development model. The requirements of the West Sumatra Regional Regulation Number 2 of 2019 concerning the Curriculum as a subject that must be relevant to Al-Quran education have been met by this e-module. They are also following Core Competence 1 in the 2013 Curriculum. Five validators use research tools in the form of questionnaires to validate this e-module. The validity test results reveal a content validation value of 0.87 and a multimedia validation of 0.92 with a valid category indicating that the developed e-module can be used as teaching materials in schools.